Optimalisasi Pemilihan Supplier Komponen Fabric pada Produk Man Shirt X Menggunakan Metode Analytical Hierarchy Process : (Studi pada PT. ABC) - Maulana Firmansyah; Yunita Primasanti; Bekti Nugrahadi (Pusat Riset dan Inovasi Nasional, 2024)
PT. ABC is a company engaged in the production of ready-to-wear clothing. The main raw materials use fabric from various suppliers. The problem is the poor quality of the fabric raw materials and late delivery from suppliers, which has an impact on production optimization. Supplier selection is a strategic activity, especially if the supplier will supply critical items and be used in the long term. Good raw materials will produce good products. Choosing the right supplier can provide benefits for the company so that the production process runs smoothly. This study aims to determine the best supplier according to the specified criteria using the Analytical Hierarchy Process (AHP) supplier selection method in the selection of fabric component suppliers at PT. ABC. Supplier selection uses the AHP method with subjective assessment input from the company. The expectation of the final result can determine the ranking of alternatives so that it produces the best supplier based on criteria that are in accordance with the company. Based on the results of processing using the AHP method, the order of criteria obtained is quality (0.6554), delivery (0.1867), and price (0.1577). The alternative selection of raw material suppliers with the highest priority is supplier X with the best score of 1.358. This shows the most optimal supplier value in fulfilling the needs of fabric raw materials according to the criteria required by the company.